KETIDAKPATUHAN PENERAPAN PEMBATASAN SOSIAL BERSKALA BESAR DI MASA PANDEMIK COVID-19 OLEH MASYARAKAT RT 001 KELURAHAN BENTENG KOTA AMBON - Hattu, Marla; Nusawakan, Dwight (Pasapua Health Journal, 2022)
Introduction: The implementation of Large-Scale Social Restrictions is a policy carried out by the government to reduce the spread of the COVID-19 virus, but in its implementation there are some people who with various reasons that are their reasons for not complying with the implementation of the policy. Method: The type of research conducted in this study is qualitative research that uses a phenomenological approach. Data collection from this study was obtained by Observation, Interview and Documentation techniques. The number of informants in this study was 10 people using the Convenience Sampling Technique chosen according to the purpose of the study, namely people who did not comply with the implementation of the PSBB during the COVID-19 Pandemic in the RT.001 neighborhood of Ambon City Fort Village, then given 12 substance questions from 3 variables related to Non-compliance with the Implementation of PSBB. This research was conducted on November 25-27, 2020. Results: The results of this study show that there are 3 things that cause people in RT.001 Kelurahan Benteng Kota Ambon not to comply with the Large-scale Social Restrictions policy, namely Meeting Basic Needs, Community Awareness and Community Perception. Conclusion: These three factors greatly affect community compliance in implementing Large-Scale Social Restrictions to prevent transmission of the COVID-19 virus because they are related to meeting the basic needs of the community which are influenced by environmental conditions